2004
DOI: 10.1590/s1415-47572004000400006
|View full text |Cite
|
Sign up to set email alerts
|

BRCA1 mutations in Brazilian patients

Abstract: BRCA1 mutations are known to be responsible for the majority of hereditary breast and ovarian cancers in women with early onset and a family history of the disease. In this paper we present a mutational survey conducted in 47 Brazilian patients with breast/ovarian cancer, selected based on age at diagnosis, family history, tumor laterality, and presence of breast cancer in male patients. All 22 coding exons and intron-exon junctions were sequenced. Constitutional mutations were found in seven families, consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 30 publications
2
13
0
3
Order By: Relevance
“…This Ashkenazi Jewish founder mutation [34,35] has been described in Dutch, Russian, French and many other populations, and a recent study showed that 245 carriers from 14 different populations presented the same haplotype, suggesting a single founder origin [36]. Indeed, this is one of the most common mutations identified in Brazilian patients to date [22,24,25], and Gomes et al [22] found 5382insC in 56% of all BRCA mutation carriers, and a very similar frequency (57%) was described by Lourenço et al [37]. A 2008 study demonstrated that seven Brazilian 5382insC carriers all shared the same haplotype [38].…”
Section: Resultsmentioning
confidence: 57%
“…This Ashkenazi Jewish founder mutation [34,35] has been described in Dutch, Russian, French and many other populations, and a recent study showed that 245 carriers from 14 different populations presented the same haplotype, suggesting a single founder origin [36]. Indeed, this is one of the most common mutations identified in Brazilian patients to date [22,24,25], and Gomes et al [22] found 5382insC in 56% of all BRCA mutation carriers, and a very similar frequency (57%) was described by Lourenço et al [37]. A 2008 study demonstrated that seven Brazilian 5382insC carriers all shared the same haplotype [38].…”
Section: Resultsmentioning
confidence: 57%
“…The high prevalence of c.5266dup was described initially in Ashkenazi Jews, and this mutation has subsequently been described in other populations from Central and Eastern Europe. Haplotype studies have demonstrated a common origin of this mutation in European populations, and several authors have described its occurrence in Brazilian breast cancer patients (Lourenço et al , 2004; Dufloth et al , 2005; Gomes et al , 2007). More recent studies indicate that the mutation was introduced into the Ashkenazi Jewish genetic pool approximately 400–500 years ago in Poland, but the mutation originated from a single common European ancestor long before (Hamel et al , 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Only two reports from Brazilian breast-cancer affected patients have suggested that a founder BRCA1 mutation, c.5266dup, may be encountered at a significant prevalence [16,17]. This mutation is the second most common mutation described in the Breast Cancer Information Core (BIC) database [28] for HBOC families worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…The women enrolled in the study were not selected for a family history of the disease, and their ancestry was not described. A previous study [16] of 47 unrelated breast cancer-affected women from Rio de Janeiro with a family history of cancer suggestive of the HBOC syndrome had already identified the BRCA1 c.5266dup mutation in a significant proportion of the mutation-positive patients (four in seven). Interestingly, none of them reported Jewish ancestry.…”
Section: Introductionmentioning
confidence: 99%